Reliability and Clinical Impact of the Normalization of the Prothrombin Times in Oral Anticoagulant Control - Loeliger, E A; Besselaar, A M H P van den; Lewis, S M (Thrombosis and Haemostasis, 1985)
In 1983, the World Health Organization (WHO) published recommendations for normalization, in oral anticoagulant control, of the prothrombin time (PT). The common denominator is the International Sensitivity Index (ISI) of a thromboplastin, obtained by means of thromboplastin calibration. The common scale is that of the International Normalized Ratio (INR). The INR is the PT ratio Patient PT/normal PT which would have been found normal PT with the WHO primary international reference preparation (IRP) 67/40. The reliability of the INR depends on the extent of calibration precision, patient-specific influences, as well as interlaboratory variation in the PT determination. Under well-controlled conditions the overall coefficient of variation (CV) of the INR is 11-13.5%, if thromboplastins of ISI ≃ 1 are used. For so-called low-sensitivity thromboplastins (ISI ≃ 2-2.5), the overall variation is larger due to a large between-laboratory variation of the measured PT-ratiosThe user of thromboplastin will be provided with a chart or graph enabling him to convert the conventional terms used for expressing PTs into INRs. For quality assurance, and to prepare his own calibration chart if necessary, he should check normalization by means of control plasmas to which INRs have been assigned.There is sufficient clinical evidence to express optimal therapeutic ranges in terms of INR. Manufacturers should revise and adapt their inserts where necessary in order to conform to these requirements.
Keywords: Oral anticoagulant control; Prothrombin time normalization; Thromboplastin calibration; Therapeutic range